Hepatotoxicity and Its Impact on Mortality in COVID-19 Patients : Hepatotoxicty in COVID-19 - Güzel, Efraim; Baydar Toprak, Oya; Aydin, Kaniye (Scientific Reports in Medicine, 2024)
Objective: "COVID-19-related liver damage" can occur frequently in course of COVID-19 disease and cause significant problems. Our study aimed to investigate prevalence of liver damage due to COVID-19, its risk variables, and the effect of liver damage on course of COVID-19 and mortality.Method: One hundred patients over eighteen years of age who were hospitalized between 01.08.2021-01.03.2022 and had positive RT-PCR tests were included in our study. Impaired liver function tests were identified as having alanine aminotransferase(ALT) and aspartate aminotransferase(AST) levels exceeding upper laboratory limits.Results: The mean age of patients included in study was 57.9 ± 14.9 years, with 49% of them being male. In our study, we had an 8% death rate and 37% of patients had abnormal liver function tests. The presence of severe disease(p